Permanent deformation behaviour of open-graded bitumen rubber asphalt using the model mobile load simulator (MMLS3). - Kasozi, Adam Matovu (Stellenbosch : Stellenbosch University, 2025)
ENGLISH ABSTRACT: Permanent deformation (rutting) has been at the centre of many pavement research projects as one of the major pavement distresses. With road transport providing a cheap and more accessible trade outlet than rail transport, pavements in South Africa have become more susceptible to permanent deformation. This has, therefore, led to different innovations regarding mix designs and binder modifications to try to combat this distress mechanism. This study covers the resistance of Bitumen Rubber Asphalt Open-Graded (BRAOG) mixes and the permanent deformation under Model Mobile Load Simulator (MMLS) wet trafficking. Bitumen rubber has been extensively used to surface heavily trafficked pavements in South Africa. The MMLS acts as the accelerated pavement tester while the BRAOG cores are immersed in hot water at 50 °C. This helps to simulate the sub-tropical and humid climatic regions. The bitumen rubber binder (A-R2) is isolated and exposed to a series of rheological tests using the Bending Beam Rheometer (BBR), Dynamic Shear Rheometer (DSR) and Rolling Thin Film Oven (RTFO). The Multiple Stress Creep Recovery (MSCR) hightemperature test evaluates the binder's response to permanent deformation. The MMLS results show that the exponential smoothing technique provides a more accurate rut profile than the conventional 3-point moving average smoothing technique. From the binder rheology, the rubber modification provided an increased elastic behaviour at high temperatures. In conclusion, the mixes deformed more than the acceptable 2 mm rutting limit specified in the MMLS testing protocols, but the binder played a crucial role in the resistance to rutting and moisture damage of the BRAOG mixes. It is recommended that more research is done to develop and expand the specifications for modified binders and MMLS rutting empirical protocols.